2015
DOI: 10.1002/cbf.3126
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA methyltransferases expression with global and gene‐specific DNA methylation in colorectal cancer cells

Abstract: There are conflicting reports regarding the association between DNA methyltransferases (DNMTs) expression and global or gene-specific DNA methylation in colorectal cancer (CRC) cells. To correlate DNMTs expression with DNA methylation, we quantified DNMT1, DNMT3A and DNMT3B mRNA levels in five CRC cell lines (HCT116, LS180, HT29/219, Caco2 and SW742) by real-time reverse-transcriptase polymerase chain reaction (PCR) assay. In addition, we examined the global 5-methyl cytosine levels and the methylation pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…As shown in Supplemental Figure S5A , EZH2 was overexpressed in Stage III–IV CRCs (1.55-fold increase, p=0.03), but not in ACF ( Supplemental Figure S5B ). We also interrogated the RNA-Seq dataset for the expression levels of the DNA methyltransferases (DNMTs), a group of genes ( DNMT1, DNMT3A and DNMT3B ) that are often up-regulated in CRC 34 . As shown in Supplemental Figure S5A&B , DNMT1 and DNMT3B are overexpressed in cancer samples, but not in ACF.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Supplemental Figure S5A , EZH2 was overexpressed in Stage III–IV CRCs (1.55-fold increase, p=0.03), but not in ACF ( Supplemental Figure S5B ). We also interrogated the RNA-Seq dataset for the expression levels of the DNA methyltransferases (DNMTs), a group of genes ( DNMT1, DNMT3A and DNMT3B ) that are often up-regulated in CRC 34 . As shown in Supplemental Figure S5A&B , DNMT1 and DNMT3B are overexpressed in cancer samples, but not in ACF.…”
Section: Resultsmentioning
confidence: 99%
“…In general, DNMTs determine the DNA methylation pattern of the genome. Alterations in the expression or epigenetic regulation of DNMTs will elicit methylation changes at both regional and global genomic levels (21,22). On the other hand, besides the classic interaction of ligand-bound ER dimers with estrogen-responsive elements in target gene promoters, estrogen also regulates gene expression via multiple nonclassic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…All of the measurements were performed in triplicate within each experiment. For more information please refer to our previously published article [2].…”
Section: Analysis Of Global Dna Methylationmentioning
confidence: 99%
“…DNA methylation is described as an epigenetic mechanism involving the transfer of methyl group at the 5′ carbon of cytosine nucleotides to form 5-methyl cytosine (5-mC) in CpG islands and modulates gene expression [1][2][3]. It has been suggested that three active forms of DNA methyltransferases (DNMT) including DNMT1, DNMT3A and DNMT3B are responsible for maintenance and generation of DNA methylation [4].…”
Section: Introductionmentioning
confidence: 99%